Porcine interferon lambda 3 (IFN-λ3) shows potent anti-PRRSV activity in primary porcine alveolar macrophages (PAMs) - Jun Zhao; Ling Zhu; Lei Xu; Jianbo Huang; Xiangang Sun; Zhiwen Xu (BMC Veterinary Research, 2020)
Abstract Background Porcine reproductive and respiratory syndrome virus (PRRSV) is a serious viral disease of swine. At present, there are vaccines for the control of PRRSV infection, but the effect is not satisfactory. The recombination of attenuated vaccines causes significant difficulties with the prevention and control of PRRSV. Type III interferons (IFNs), also called IFN-λs, were newly identified and showed potent antiviral activity within the mucosal surface and immune organs. Results Therefore, primary porcine alveolar macrophages (PAMs) were used for this investigation. To this end, we found that the replication of PRRSV in PAMs was significantly reduced after pre-treatment with IFN-λ3, and such inhibition was dose- and time-dependent. The plaque formation of PRRSV abrogated entirely, and virus yields were reduced by four orders of magnitude when the primary PAMs were treated with IFN-λ3 at 1000 ng/ml. In addition, IFN-λ3 in our study was able to induce the expression of interferon-stimulated genes 15 (ISG15), 2′-5′-oligoadenylate synthase 1 (OAS1), IFN-inducible transmembrane 3 (IFITM3), and myxoma resistance protein 1(Mx1) in primary PAMs. Conclusions IFN-λ3 had antiviral activity against PRRSV and can stimulate the expression of pivotal interferon-stimulated genes (ISGs), i.e., ISG15, Mx1, OAS1, and IFITM3. So, IFN-λ3 may serve as a useful antiviral agent.